2020
DOI: 10.3390/nano10030432
|View full text |Cite
|
Sign up to set email alerts
|

Mineral-Doped Poly(L-lactide) Acid Scaffolds Enriched with Exosomes Improve Osteogenic Commitment of Human Adipose-Derived Mesenchymal Stem Cells

Abstract: Exosomes derived from mesenchymal stem cells are extracellular vesicles released to facilitate cell communication and function. Recently, polylactic acid (PLA), calcium silicates (CaSi), and dicalcium phosphate dihydrate (DCPD) have been used to produce bioresorbable functional mineral-doped porous scaffolds-through thermally induced phase separation technique, as materials for bone regeneration. The aim of this study was to investigate the effect of mineral-doped PLA-based porous scaffolds enriched with exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 84 publications
0
62
0
Order By: Relevance
“…Although a combined mechanism is likely, future works should determine the origin of these components. In addition, recent works reported the use of biomaterials enriched in human cell exosomes, and exosome-enriched natural and synthetic scaffolds demonstrated to provide internal and external modulation factors able to enhance regeneration of dental tissues [31]. These findings point out the possibility that exosomes released from the tissue explants could play a beneficial role on development, maturation, and differentiation of the fibrin-garose biomaterial used in our functionalized tissue model.…”
Section: Discussionmentioning
confidence: 55%
“…Although a combined mechanism is likely, future works should determine the origin of these components. In addition, recent works reported the use of biomaterials enriched in human cell exosomes, and exosome-enriched natural and synthetic scaffolds demonstrated to provide internal and external modulation factors able to enhance regeneration of dental tissues [31]. These findings point out the possibility that exosomes released from the tissue explants could play a beneficial role on development, maturation, and differentiation of the fibrin-garose biomaterial used in our functionalized tissue model.…”
Section: Discussionmentioning
confidence: 55%
“…Highly porous poly-lactic acid scaffolds doped with bioactive calcium silicates and calcium phosphates have been recently designed [28,29] and demonstrated the ability to be colonized by oral derived mesenchymal stem cells and to stimulate their shift through osteogenic lineage [27,36]. Calcium silicates/poly-e-caprolactone 3D printed scaffolds designed for dental pulp tissues revascularization purposes showed good dental pulp stem cell proliferation and osteogenic differentiation [37].…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that EHG could effectively retain exosomes inside the hydrogel, and over 1 × 10 10 mL –1 of exosomes per day were released, resulting in the acceleration of cartilage defect repair ( Liu X. et al, 2017b ). Another study by Gandolfi et al (2020) produced mineral-doped PLA-based scaffolds enriched with EVs to evaluate the osteogenic effects on hAD-MSCs. They showed a dynamic change after depositing exosomes on the surface of the scaffold; as the PLA matrix partially degraded, the formation of a calcium phosphate layer partially filled the pores and led to a decrease in porosity, which influenced the biological behavior of the hAD-MSCs.…”
Section: Methods For the Modification Of Biomaterials To Facilitate Ementioning
confidence: 99%
“…Another study by Gandolfi et al (2020) produced mineral-doped PLA-based scaffolds enriched with EVs to evaluate the osteogenic effects on hAD-MSCs. They showed a dynamic change after depositing exosomes on the surface of the scaffold; as the PLA matrix partially degraded, the formation of a calcium phosphate layer partially filled the pores and led to a decrease in porosity, which influenced the biological behavior of the hAD-MSCs.…”
Section: Pore Parametersmentioning
confidence: 99%